Mechanism for particle fractionalization and universal edge physics in quantum Hall fluids - Arkadiusz Bochniak; Zohar Nussinov; Alexander Seidel; Gerardo Ortiz (Communications Physics, 2022)
Fractional quantum Hall states are the best known examples of emergent quantum matter with topological order. Here, the authors present a fusion mechanism for particle fractionalization and a conjecture on the universal long-distance behavior of edge excitations in fractional quantum Hall fluids.